Social Media-Based Nature Tourism Village Marketing Management Training - Setiawan, Ari; Endah Emiarti; Pretty Diawati; Vera Selviana Adoe; Arief Andy Soebroto; Romanda Annas Amrullah; Farida Mony; Bioni Sena; Nurasiah; Alfry Aristo Jansen Sinlae (IMPACTS: International Journal of Empowerment and Community Services, 2025)
ABSTRACT Purpose Ngudal Tourism Village in Tawangmangu, Central Java, possesses high potential for nature-based tourism due to its scenic landscapes and cultural richness. However, its digital presence and promotional strategies remain limited. This community service program aimed to enhance the digital marketing capacity of local tourism stakeholders through social media-based training. Methods - Fifteen participants—including homestay owners, youth representatives, culinary business actors, and village officials—were trained in content creation, platform management, audience engagement, and digital branding. The training adopted a participatory approach involving workshops, simulations, and mentoring. Result and discussions - As a result, participants demonstrated significant improvements in digital literacy, with post-training assessments showing a 47% increase in knowledge. The village launched official Instagram, Facebook, and YouTube accounts, achieving over 300 organic followers and substantial content engagement within one month. Economic impacts included increased homestay bookings and product inquiries via social media. A digital task force was formed to ensure sustainability. Conclusion - This program illustrates the potential of social media as a transformative tool for rural tourism promotion and recommends replicating such models in other under-promoted villages to foster inclusive digital development.